2015
DOI: 10.1016/j.neurobiolaging.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing human vestibular sensory epithelia for experimental studies: new hair bundles on old tissue and implications for therapeutic interventions in ageing

Abstract: Balance disequilibrium is a significant contributor to falls in the elderly. The most common cause of balance dysfunction is loss of sensory cells from the vestibular sensory epithelia of the inner ear. However, inaccessibility of inner ear tissue in humans severely restricts possibilities for experimental manipulation to develop therapies to ameliorate this loss. We provide a structural and functional analysis of human vestibular sensory epithelia harvested at trans-labyrinthine surgery. We demonstrate the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 84 publications
10
54
0
4
Order By: Relevance
“…3 months of age, an increasing number of hair bundles contained very long, thick structures indicating fusion and elongation of stereocilia and fusion of stereocilia with the kinocilium (Fig 10A–10E). Similar fused, elongated stereocilia were present in the maculae of older normal animals (Fig 10F) and have been described in other studies of age-related effects upon macular hair cells [39]. Likewise, stereocilia in the anomalous bundles of cochlear IHC, particularly those in the apical coils, appeared to increase in length with age; by 6 months the height of longer stereocilia in the bundles was ca.…”
Section: Resultssupporting
confidence: 86%
“…3 months of age, an increasing number of hair bundles contained very long, thick structures indicating fusion and elongation of stereocilia and fusion of stereocilia with the kinocilium (Fig 10A–10E). Similar fused, elongated stereocilia were present in the maculae of older normal animals (Fig 10F) and have been described in other studies of age-related effects upon macular hair cells [39]. Likewise, stereocilia in the anomalous bundles of cochlear IHC, particularly those in the apical coils, appeared to increase in length with age; by 6 months the height of longer stereocilia in the bundles was ca.…”
Section: Resultssupporting
confidence: 86%
“…Human inner ear tissue (cochlea and vestibular endorgans) obtained from ablative surgery has been useful to investigate the expression of several proteins by IHC, mRNA (Ishiyama et al 2010; Calzada et al 2012b; Liu et al 2015, 2016), and ultrastructural organization of the auditory and vestibular sensory epithelium (Ishiyama et al 2007; McCall et al 2009; Liu et al 2015; Taylor et al 2015). Studies of Cx distribution in the human cochlea: IF and confocal microscopy analysis of Cx proteins in the human cochlea have shown that Cx26 and Cx30 proteins are co-expressed (Liu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-mount immunostained specimens have also been used to conduct TEM (Nadol et al 1993; McCall et al 2009; Taylor et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Golub et al [133] estimated that 17% of hair cells were replaced in utricles of adult mice. Further, there is morphological evidence that humans, even those who are very old, have the capacity to form new utricular hair cells [137]. This is in stark contrast to the nearby cochlea, in which no hair cells are replaced after damage in adulthood [101] (Fig.…”
Section: Spontaneous Regeneration Of Vestibular Hair Cells After Dmentioning
confidence: 99%